Pertanggungjawaban Orang Tua Akibat Transaksi Pembelian Secara E-Commerce Yang Dilakukan Oleh Anak Dibawah Umur - Panjaitan, Wijaya Natalia (Bacarita Law Journal, 2024)
E-commerce purchase transactions by minors children are often carried out because of the facility of access to technology that is not supervised by parents or occurs due to the negligence of parents. The purpose of this research is to analyze how the responsibility of parents due to e-commerce purchase transactions made by minors. The research method used in this research is normative juridical by analyzing and reviewing legal sources based on literature such as applicable laws, law books and journal articles. The results of the research state that e-commerce purchase transactions made by minors are invalid because they violate the subjective conditions in Article 1320 of the Civil Code and all legal consequences caused are the parents' responsibility.